Optimization of subarachanoid block by oral pregabalin for hysterectomy - Monica Kohli; T Murali; Rajni Gupta; Parveez Khan; Jaishri Bogra (Wolters Kluwer Medknow Publications, 2011)
Background: 80% of patients undergoing surgical procedures experience postoperative pain 1 and requires adequate pain relief. Nowadays drugs like COX2 inhibitors and calcium channel modulators (Pregabalin and Gabapentin) are been increasingly used for postoperative pain management effectively. We conducted this study to find whether preoperative pregabalin has any effect in postoperative analgesic requirement in patients undergoing hysterectomy under spinal anaesthesia. Patients & Methods: This randomized, double-blind, placebo-controlled trial was conducted in 150 patients undergoing hysterectomy under spinal anaesthesia, divided in three groups - Group I (PO) - Control group, Group II (P150) received 150 mg pregabalin and Group III (P300) received 300 mg pregabalin. We used VAS for anxiety, Ramsay sedation scale and VAS for patient satisfaction regarding pain relief. Results: There was significant reduction in anxiety in groups P (150) and P (300) than placebo group P (0) during intraoperative and postoperative period than preoperative period. There was significant sedation seen in groups P (150) and P (300) than placebo group P (0). First rescue analgesia in group P (300) was202.42±6.77 and in group P (150) was176.38±4.80on average, group P (0) was131.38±5.15. Dizziness was 44.44% in group P (300), 36.11% in group P (150), and 19.44% in group P (0). Patient satisfaction was better in P (300) group than other two groups. Conclusions: Pregabalin being an oral drug which would be easy for the patients to take and also its prolongation of the neuraxial block helps in immediate postoperative analgesia and further reduction of other parentral analgesics. Pregabalin 150mg would be the optimal preemptive dose for hysterectomy under spinal anaesthesia.